JASLARDÍŃ PUQARALÍQ BELSENDILIGIN TÁMIYINLEWDIŃ HUQÍQÍY TIYKARLARÍ - Orınbetov, Nietulla Turdımuratovich (SCIENCE and SOCIETY, 2026)
This article analyzes the formation of the civic position of youth in the context of New Uzbekistan. It reviews reforms aimed at developing legal awareness and active civic engagement among young people, outlines key directions of state youth policy, and examines the legal framework regulating this sphere.